2017
DOI: 10.1097/md.0000000000007884
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of nanoparticle albumin-bound paclitaxel regimens for relapsed small cell lung cancer

Abstract: Although small cell lung cancer (SCLC) is initially sensitive to chemotherapy, it recurs in most cases. Standard regimens for salvage chemotherapy have not been established, and the prognosis of relapsed SCLC remains poor. In the present study, we investigated the clinical efficacy and safety of nanoparticle albumin-bound paclitaxel (nab-paclitaxel) regimens for the treatment of relapsed SCLC.In this retrospective multicenter analysis, 14 patients (3 women and 11 men; median age 71 years) with relapsed SCLC re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 22 publications
1
19
1
Order By: Relevance
“…These data confirmed the unfavourable prognostic role of CNS involvement, especially in relapsed SCLC. Our results were similar to those reported from a retrospective study 18 in which 9 of the 14 enrolled patients were treated with nab-paclitaxel, as third-line or later. In this subgroup, ORR, mPFS and mOS were 11%, 2.0 months and 4.0 months, respectively.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These data confirmed the unfavourable prognostic role of CNS involvement, especially in relapsed SCLC. Our results were similar to those reported from a retrospective study 18 in which 9 of the 14 enrolled patients were treated with nab-paclitaxel, as third-line or later. In this subgroup, ORR, mPFS and mOS were 11%, 2.0 months and 4.0 months, respectively.…”
Section: Discussionsupporting
confidence: 90%
“…Three Asian retrospective analyses conducted in relapsed SCLC patients showed some anti-cancer activity of nab-paclitaxel. [18][19][20] Since nab-paclitaxel has not been prospectively studied in relapsed SCLC yet, we designed this open-label, prospective Phase 2 trial with the aim to assess its activity and safety in patients with both refractory and sensitive disease.…”
Section: Introductionmentioning
confidence: 99%
“…Efficacy in SCLC transformation patients was poorer than that in primary SCLC patients 15. It was reported that bevacizumab combined with chemotherapy was effective in SCLC in first-line treatment 16,17. In our case, we found apatinib was available in patients with SCLC transformation (Figure 5E).…”
Section: Discussionmentioning
confidence: 56%
“…When used clinically, it causes severe side-effects such as leucopenia. thrombocytopenia, neutropenia and fatigue (4) and anorexia and constipation (5). Patients who received platinum treatment with a taxane were more likely to experience grade 2 to 4 neuropathy (6).…”
mentioning
confidence: 99%